PERSEPSI PENGUNJUNG KAMPUNG KEREN TERHADAP KEGIATAN KOMUNIKASI PEMASARAN PEMKOT KEDIRI DALAM MEMPROMOSIKAN KAMPUNG KEREN - Kellina Mahadewi (INFOKOM (Informatika & Komputer), 2023)
ABSTRACTBackground: The concept of downtown tourism is currently being developed by the Kediri CityGovernment to enlighten the surrounding community, named Creative and Independent Village(Kampung Keren) program since 2021. This topic is interesting for research because thedetermination of Kampung Keren was not accompanied by an effective communication program.The government does not provide special media that fully exposes Kampung Keren. The lack ofmarketing communication activities can certainly affect visitors' perceptions of Kampung Keren.Purpose: This study was structured to describe visitors' perceptions of Kampung Keren towardsmarketing communication activities carried out by the Local Government in promoting KampungKeren. The theory used also discusses marketing communications and perceptions. Method: Themethod used in this study is qualitative with a descriptive type, while data collection techniquesare carried out by observation, in-depth interviews, and literature studies. Results: Based on theresults of this study, visitors only know about marketing communication activities through the IGKediri City Government and the website only. Visitors also gave good responses to the activitiescarried out, although there were still informants who assessed that marketing communicationactivities were still lacking and needed improvement. Conclusion: Based on information that hasbeen uploaded, it is possible for the public's perception of Kampung Keren's marketingcommunications to have a positive value. Keywords: perception, marketing communications, visitors, Kampung Keren.